Preliminary study on the comparable flow pattern between stented and non-stented aneurysm at hypertension condition - Taib, I. (2013)
The presence of the vortex formation associated with high pressure gradient has aggravated the rupture at the aneurismal wall. In order to decrease the possibility of aneurysm to be rupture, device like wire-mesh called stent was inserted at the aneurysm bulge. This study was focused on investigates the hemodynamic factor especially pressure distribution toward the failure of the aneurismal wall. Computational fluid dynamics method has used to identify the influence of the hemodynamic factor at the aneurysm. The results of this study shown the slightly decrease of the pressure distribution after the insertion of the bare metallic stent (BMS). The results on non-stented aneurysm was depicted the strong vortex was dominated the entire region of aneurysm. The strength of the vortex also was seems very weak after the insertion of this stent. The flow visualization between stented and non-stented aneurysm has given a good features in deep understanding of hemodynamic effect on the aneurismal wall. From the observed, the insertion of the stent manages to reduce the stress that exerted to aneurismal wall as well as decreased the strength of the vortex formation.